Surgical Health Needs of Minor Refugees in Germany: A Cross-Sectional Study - Loucas, Marios; Loucas, Rafael; Muensterer, Oliver J. (European Journal of Pediatric Surgery, 2018)
Introduction There has been a substantial rise in refugees entering Germany over the past years, of which approximately one-third are underaged. Many end up in pediatric surgical care, and little is known about the health of these individuals. Our study was designed to assess the surgical-related health status of underage refugees based on a large sample cohort.Materials and Methods After ethics board approval, we used a structured questionnaire to collect demographic information and surgical health-related elements in three large refugee accommodation centers.Results A total of 461 minor refugees were included. The majority were boys (54.5%) with an average age of 8 years. Out of the eight recorded countries of origin, most children came from Syria (33.6%) followed by Afghanistan (23.2%). Previous operative interventions were recorded in 42.2% of participants. Among girls, 11% suffered genital mutilation. Trauma was common and the most common mechanism was a fall from bicycle (38%) followed by burn injuries (7.4%). Up to 20% of them experienced physical violence during the flight or in the accommodation facility. Vaccination rates varied widely according to origin. Of the participants, only 63% were vaccinated according to schedule. Chronic diseases were found in only 13% of the study cohort, anemia being most prevalent at 4%.Conclusion Minor refugees have specific health-related problems that must be considered to ensure appropriate medical care. Many refugee children were victims of physical violence and many girls suffered genital mutilation. Vaccination status is unreliable; therefore, tetanus vaccination should always be considered when these patients seek pediatric surgical care. Tailored anticipatory guidance should be provided to this patient population.
Keywords: refugee; children; vaccination; genital mutilation; trauma